Large Scale Projects in eHealth. - Blobel, B. (IOS Press, 2012)
The efficient and effective delivery of healthcare requires accurate and relevant methodologies; eHealth projects contribute to the success and sustainability of tomorrow's health care systems. EFMI Special Topic Conferences (STC) provide a forum for discussing achievements and experiences on specific topics in medical informatics. This book presents the proceedings of the EFMI STC 2012, held in Moscow, Russia, in April 2012. The theme of this STC is the implementation experience of large scale eHealth projects. These large scale projects can be described by size, effects, complexity, duration.